Peningkatan Keterampilan Membaca Pemahaman Peserta Didik Menggunakan MetodeThe Learning Cell di Sekolah Dasar - Sari, Reni Novita; Muhammadi, Muhammadi; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated because of the low ability to read at a glance the students of class IV SDN 04 pisang Kota Padang. The low ability to read at a glance because students have not implemented the correct reading stage of the pre-reading stage, when read, and after reading. Therefore, this study aims to describe the ability to read at a glance with the The learning cell  method in the IV SDN 04 Pisang Kota Padang class. This research is a classroom action research using qualitative and quantitative approach. Subject of the research teacher and 28 students of class IV SDN 04 Pisang. The results of this study indicate that the ability to read at a glance the students increased from 74.0 (Enough) with 75.9% completeness in cycle I, to 81.7 ( good) with 85,0% completeness in cycle II. Percentage increase from cycle I to cycle II is 22.5%. Based on these results, it can be concluded that the the learnin cell method can improve the ability to read at a glance the grade IV students of Elementary School. Keywords: Reading Ability At a glance; The Learning Cell